The Effect of The Implementation of Google Classroom Digital Media for The Easy of Teachers in Assessing Learning Outcomes - Evi Aulia Rachma; Ratna Nurdiana; Abdul Ghofur (Universitas Djuanda, 2020)
The rapid development of technology demands innovation and creativity in learning activities. Especially in the midst of a pandemic such as this time learning activities must still be carried out by implementing learning activities from home. Online learning by utilizing technology becomes a solution in overcoming these problems. One way that can be used to do the learning process online is to use Google Classroom digital media. This study aims to determine the effect of the application of Google Classroom digital media on the ease of teachers in assessing student learning outcomes. The research approach used is a quantitative approach with descriptive methods. This research involved 50 elementary grade IV teachers in Lamongan District. Data collection techniques used in this study include a closed questionnaire. Based on the results of the analysis discussed, it is known that t count> t table = 6,066> 1,970. So it can be concluded that the application of Google Classroom digital media influences the ease of teachers in the assessment of learning outcomes. Google classroom makes it easy for teachers to monitor student learning activities without being bound by time limits or class hours.